Ethical standards and guidelines for the use of artificial intelligence in public relations - Verčič, Dejan (knjige, 2025)
This Gold Paper provides a snapshot of the situation in 2024 and outlines a roadmap for proactive and responsible behavior in professional public relations and strategic communication.
Keywords: elektronske knjige; Etični vidik; Odnosi z javnostmi; smernice; standardi; Umetna inteligenca; Uporaba